Moving to improve mental health - The role of exercise in cognitive function: A narrative review - Venkateswar Pujari (Wolters Kluwer Medknow Publications, 2024)
This review study investigates how exercise can enhance cognitive ability and mental wellness. Physical activity has been linked to a number of beneficial effects on cognitive function, including increased memory and executive function in adults, improved academic performance in children and adolescents, and potential advantages for people with cognitive impairments or neurodegenerative diseases. Increased cerebral blood flow, the synthesis of neurotrophic factors, and a decrease in oxidative stress and inflammation are the processes driving these effects. Studies have shown that exercise has mood-regulating benefits, with symptoms of anxiety and sadness lessening as a result. These mood-enhancing effects are a result of the endocannabinoid system being activated, endorphins being released, and changes in self-esteem and body image. Exercise therapies have also demonstrated the potential to encourage cognitive health as people age and lower the likelihood of cognitive decline. Exercise has been investigated as an adjuvant treatment for mental health illnesses, such as depression, anxiety disorders, schizophrenia, bipolar disorder, and eating disorders, in addition to its preventive effects. Exercise can improve the effectiveness of treatment and general wellbeing when it is incorporated into comprehensive treatment strategies. To identify the ideal exercise parameters for certain outcomes and overcome barriers to exercise participation, more study is necessary. We can get closer to enhancing general wellbeing and quality of life by including exercise in measures for promoting mental health and cognitive health.